RECORDING OF PARASTIC AND FUNGAL INFECTIONS IN THREE FISH FARMS, SOUTH OF BAGHDAD - ASMAR, K. R.; BALASEM, A. N.; AL-JUWDA, J. M.; ADDAY, T. K. (Iraqi Journal of Aquaculture, 2022)
Between January and August 2002, a total of 74 fishes belonging to nine species (Alburnus caeruleus, Barbus luteus, B. sharpeyi, Carassius auratus, C. carassius, Ctenopharyngodon idella, Cyprinus carpio, Hypophathalmichthys molitrix and Liza abu) were collected from three fish farms south of Baghdad. Twenty-six species of parasites were observed.They were following : Three species of protozoa ( Ichthyophthirius multifiliis , Trichotina domerguei, Muxobolus nemchili), fifteen species belonged to monogenetic trematodes (Dactylogyrus achmerowi, D. anchoratus, D. arcuatus, D. baueri, D. dulkeiti, D. formosus, D. hypophathalmichthys, D. intermedius, D. lamellatus, D. minutus, D. solidus, D. varcohini, D. dvastator, Gyrodactylus baicalensis, G. elegans), three species belonged to digenetic trematodes (Diplostomum commutatum, D. phoxini, D. spathacum), one species of acanthocephala ( Neoechinorhynchus iraqensis ) and four crustacea (Ergasilus mosulenis, E. sieboldi, Ergasilus sp., Lernaea cyprinacea ). Moreover, two fungal species (Ichthyophonus hoferi ,Saprolegnia sp.). The observation of Dactylogyrus formosus and D. intermedius were regarded as the first record in Iraq. Meanwhile five new hosts for 18 species of parasites were described in the present study. However, most species of parasites were isolated from Cyprinus carpio (14 species).